The Impact of the Covid 19 Pandemic on Consumer Behaviour in the Vietnam Market - Thy, Nguyen Thi Anh (Advances in Social Sciences Research Journal, 2021)
This study was conducted to identify new trends in the consumer behaviour in Vietnam under the impact of the Covid 19 epidemic. The pandemic has impacted many aspects of working, communication, and contacting. This has also changed purchasing habits such as product preferences and the way of buying things. The changes in consumer behaviour in the Vietnam market have similar characteristics to the world market but still have their own characteristics. Therefore, the aim of this study is to find out these changes and suggest implications for businesses to better meet consumer demands as well as contribute to building positive experiences in shopping during the pandemic. In addition, the study also impresses the significance of having more studies about the impact of Covid 19 on consumers to have more thoughtful understand about the market in Vietnam